Faktor-Faktor yang Memengaruhi Repurchase Intention pada Pengguna Netflix - Jenny Surya Karnisya; Corry Yohana; Sabo Hermawan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of the post-pandemic information ecosystem, especially digital media field has fueled the massive growth of video-on-demand platforms in Indonesia. This phenomenon is supported by data from We Are Social (2025), which indicates that 34.7% of internet penetration in Indonesia prioritizes spending on movie streaming. Amidst intense market competition, Netflix has emerged as one of the most popular platforms. This study aims to analyze the influence of social media marketing, perceived usefulness, and e-service quality on repurchase intention through customer satisfaction of Netflix Generation Z users in DKI Jakarta. The approach chosen for this study was a survey method with 190 respondents selected using a purposive sampling technique. Data were collected through an online questionnaire with a six-point Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS4. The results showed that perceived usefulness directly influences repurchase intention. Meanwhile, social media marketing and e-service quality did not significantly influence repurchase intention, which means it must be bridged by customer satisfaction. These findings indicate that Generation Z's repurchase intention is more influenced by the ease of use of the system and perceived functional benefits than by marketing through social media.